2009
DOI: 10.1103/physrevb.79.064504
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic ordering and structural phase transition inBa2Fe2As2with Sn incorporated from the growth flux

Abstract: Neutron diffraction experiments have been carried out on a Sn-flux grown BaFe 2 As 2 single crystal, the parent compound of the A-122 family of FeAs-based high-Tc superconductors. A tetragonal to orthorhombic structural phase transition and a three dimensional long-range antiferromagnetic ordering of the iron magnetic moment, with a unique magnetic propagation wavevector k = (1, 0, 1), have been found to take place at ~90 K. The magnetic moments of iron are aligned along the long a axis in the low temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
124
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 22 publications
16
124
0
1
Order By: Relevance
“…1). The average high temperature (between 300 K and 150 K) thermal expansion coefficients can be also estimated from the published scattering data [25]. For the c-axis, both sets of data are very close, whereas for the a-axis the scattering data give the value of the average thermal expansion coefficient factor of 2 -3 times lower than that presented here.…”
supporting
confidence: 49%
“…1). The average high temperature (between 300 K and 150 K) thermal expansion coefficients can be also estimated from the published scattering data [25]. For the c-axis, both sets of data are very close, whereas for the a-axis the scattering data give the value of the average thermal expansion coefficient factor of 2 -3 times lower than that presented here.…”
supporting
confidence: 49%
“…What subtle, or striking, modifications in structure or magnetism occur with doping or pressure, and how are they related to superconductivity? Similar to other members of the AFe 2 As 2 (A=Ba, Sr) family, 5,6,7,8 at ambient pressure CaFe 2 As 2 undergoes a transition from a non-magnetically ordered tetragonal (T) phase (a = 3.879(3)Å, c = 11.740(3)Å) to an antiferromagnetic (AF) orthorhombic (O) phase (a = 5.5312(2)Å, b = 5.4576(2)Å, c = 11.683(1)Å) below approximately 170 K.9,10 In the O phase, Fe moments order in the so called AF2 structure 11 with moments directed along the aaxis of the orthorhombic structure.10 Neutron powder diffraction measurements 12 of CaFe 2 As 2 under hydrostatic pressure found that for p>0.35 GPa (at T=50 K), the antiferromagnetic O phase transforms to a new, non-magnetically ordered, collapsed tetragonal (cT) structure (a = 3.9792(1)Å, c = 10.6379(6)Å) with a dramatic decrease in both the unit cell volume (5%) and the c/a ratio (11%). The transition to the cT phase occurs in close proximity to the pressure at which superconductivity is first observed.…”
mentioning
confidence: 70%
“…Magnetism in nonsuperconducting samples at 0 x 0.03 Figure 2 shows representative low-temperature ZF-μSR spectra of the Ba(Fe 1−x Co x ) 2 As 2 crystals that give an overview of how the AF order evolves as a function of the Co substitution. In the undoped parent compound, at x = 0, it has been established by magnetic neutron diffraction that a long-range AF order with an Fe moment of about 0.9-1 μ B develops below T N = 134 K. 13,[52][53][54][55] The corresponding ZF-μSR spectrum in Fig. 2(a) is also characteristic of a bulk, long-range ordered AF state.…”
Section: Resultsmentioning
confidence: 95%